IMPLEMENTATION OF PARTICIPATORY PLANNING IN MAKING DEVELOPMENT IN TELLUMPANUA VILLAGE, TANTE RILAU DISTRICT, BARRU DISTRICT - Wahyul AZ (P3M Stia Al Gazali Barru and Meraja media, 2021)
[Full Paper] to pdf Copyright (c) 2021 Meraja journal